Standard Of Equipment Of Traffic Control And Sterilization Of Ketapang Ferry Port, Banyuwangi Regency, East Java Province - Yohan Wibisono; Ferdinand Pusriansyah; Sri Kartini; Kukuh Oktanugrah Try Wiyono (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
Ferry Port is a port specifically used for ferry transportation using Roro ships. Ketapang Ferry Port has an important role for the community because it is a Ferry Port that organizes crossings using ships to connect the islands of Java and Bali to travel such as work, tourism, or supply of agricultural products such as food, building materials and so on. The existence of the Ketapang Ferry Port will support economic development and the development of community activities as well as the growth of the population area (Hinterland). In its implementation, there are still many people who enter the port freely which should only be entered or passed by port officials and port service users who already have tickets to cross. This is very dangerous for service users and traders themselves. And there are still crossings between vehicles that will enter or leave the dock and the lack of supporting facilities for sterilization and traffic management at the Ketapang Ferry Port such as sign facilities. This is due to the lack of regulation regarding the zoning system, traffic flow patterns and traffic sign arrangements in accordance with the regulations, namely the Regulation of the Minister of Transportation Number 29 of 2016 concerning Fertilization of Ferry Ports, Decree of the Director General Number 242 of 2010 concerning Technical Guidelines for Crossing Traffic Management and Regulations. Minister of Transportation of the Republic of Indonesia Number 13 of 2014 concerning Traffic Signs. Port sterilization and management of traffic flow patterns as well as regulation of traffic signs are very important things at the ferry port in order to create a safe, comfortable, orderly and smooth ferry port.